A MODERN TREATY IN THE MARITIMES: IS IT TIME? - Nicholas, Graydon (Journal of New Brunswick Studies / Revue d'etudes sur le Nouveau-Brunswick)
This speech was intended to share my experiences as an Indigenous lawyer in New Brunswick. It includes my work with the Union of New Brunswick Indians in research on treaty rights. It is a personal reflection of experiences defending Indigenous persons in the exercise of their treaty rights in the courts in New Brunswick and the Supreme Court of Canada. It is a nutshell of the various interactions of those involved in politics, federal and provincial government representatives, and law enforcement agencies in the 1970s and 1980s. It advocates for the implementation of rights within the United Nations Declaration on the Rights of Indigenous Peoples (2007) and the Truth and Reconciliation Commission: Calls to Action (2015). It concludes that this is not the time for a modern treaty in New Brunswick.